Web able library catalog For elementary schools / Norani Wahid - Norani, Wahid (2004)
WALC is a Web Abled Library catalog and it is designed focuses on elementary school children as the aimed users.The main purposes in developing this library catalog are to facilitate information seeking of the elementary school children, to improve the management school libraries and to upgrade the quality of elementary school libraries by fulfilling the user requirements.Basically, the primary objective for this project development is to establish and develop a suitable or ideal library catalog at elementary level. One survey carried out shows that students seldom use the catalog cards to search for library materials and most of them never use Online library systems.The WALC interface is carefully designed in order to meet the school children levels and abilities. It is hoped that the expected outcome will be able to improve the management and function of elementary school libraries.